Studies on western Pacific gorgonians (Anthozoa: Octocorallia: Chrysogorgiidae). Part 2: unexpected diversity of the genus Iridogorgia in the tropical western Pacific with descriptions of two new species - Xu, Yu; Watling, Les; Zhan, Zifeng; Xu, Kuidong (Zootaxa, 2025)
Species of the genus Iridogorgia Verrill, 1883 are typical deep-sea organisms, characterized by monopodial and spiral axis with a brilliant iridescence. Utilizing an integrated morphological-molecular approach, twelve specimens of Iridogorgia obtained from the tropical western and central Pacific were described as two new species I. curva sp. nov. and I. chewbacca sp. nov., and four known species. Additionally, I. fontinalis Watling, 2007 and I. splendens Watling, 2007 are two new recorded species in the Western Pacific Ocean. Iridogorgia verrucosa Xu, Zhan & Xu, 2021 and I. squarrosa Xu, Zhan, Li & Xu, 2020 are described again. There are currently fourteen species of Iridogorgia with twelve species in the Pacific. Among them, ten species were found in the tropical western Pacific, showing a high diversity. This study indicates the direction of growth (clockwise or counter-clockwise) is not a useful taxonomic character for Iridogorgia species identification. Phylogenetic analyses, based on both mtMutS-cox1 and 28S rDNA sequences, substantiated the taxonomic designation of the new species, I. chewbacca sp. nov. However, the mtMutS and mtMutS-cox1 showed very limited usefulness for species delimitation and inner relationship inference of most Iridogorgia species, while the 28S rDNA showed much higher level of genetic variation.